Determining the effect of frailty on survival in advanced ovarian cancer: study protocol for a prospective multicentre national cohort study (FOLERO) - Daniel Hunde; Niklas Ekerstad; Mihaela Asp; Päivi Kannisto; Madelene Wedin; Charlotte Palmqvist; Pernilla Dahm-Kähler; Yvonne Brandberg; Mirna Abraham-Nordling; Kristina Åhlund; Vilhelm Mörlin; Nina Groes-Kofoed; et al. (Acta Oncologica)
Background and purpose: There is an urgent need to improve patient-selection to surgical treatment in advanced ovarian cancer as our results showed that cytoreductive surgery was without effect or even detrimental in a yet unknown subgroup of women. With an ageing population, 30% of women with advanced ovarian cancer in Sweden are >75 years. Nevertheless, there are no recommendations on patient-selection, albeit treating an unselected population in a public and centralized health care setting. Little attention has been placed on frailty assessments in oncology, despite their potential to stratify the risk of adverse outcome and mortality. Consequently, we hypothesize that frailty is a predictor of poor survival.